KARAKTERISTIK, POTENSI GENERASI MILENIAL DAN PERSPEKTIF PENGEMBANGAN PERTANIAN PRESISI DI INDONESIA - Joula Sondakh; Janne H.W. Rembang; nFN Syahyuti (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2020)
Precision agriculture requires appropriate characters of human resources to implement it. It is an integrated agricultural system based on information and production to increase business efficiency, productivity and profitability. The concept of precision agriculture, as one of the latest agricultural technology packages, was born along with the emergence of the millennial generation, namely those born between 1980 and 2000.This paper discusses the character of precision agriculture and necessity to apply it and its link to the millennial generation in terms of their character suitability and capacity. Application of precision agriculture requires the millennial generation’s ability to create, engineer and operate modern agricultural systems based on this new technology. Applying precision agriculture in Indonesia deals with various characteristics of the millennial generation due to different regional and socio-economic conditions. The government should provide infrastructure and conduct millennial farmers training to achieve social, economic, and environmental benefits of precision agriculture implementation.